A Tardy Uptake - Freadman, Anne (Discourse and Writing/Rédactologie, 2020)
Following Carolyn Miller’s (1984) definition of genre as social action, subsequent work in the field of rhetorical genre theory has focused on two aspects of her account. The first is the claim that “a genre is a rhetorical means for mediating private intention and social exigence” (Miller, 1984, p. 163). The site of this mediation is now referred to as the subject—a term that is imported from psychoanalysis and critical social theory. I am concerned that the theoretical freight carried by this term—with its claim to address the “big questions” of subjectivity—diverts us from our focus on “how the genre works as rhetorical action” (Miller, 1984, p. 159). I shall replace the subject with the agent, moving then to argue that bringing uptake to bear on agency helps shift the debate to a more strictly rhetorical terrain. The second aspect that has been focused on is exigence: the “social motive” of rhetorical action, “an objectified social need” lying at “the core of situation” (Miller, 1984, pp. 158, 157). I consider an ambiguity at the heart of this concept of exigence between the work it does in accounting for punctual rhetorical action—the genre in actu—and its work in generalizing over some genre in virtu. Because of this, I move to replace exigence with alternative ways of conceiving the site of rhetorical action. Throughout, I accept broadly the framework of Rhetorical Genre Studies. While I seek to solve the problems through a rigorous reliance on rhetoric, I move beyond this frame when I discuss the restrictions on a theory of genre imposed by an exclusive assumption of verbal or discursive acts.